1990
DOI: 10.1017/s0033291700017037
|View full text |Cite
|
Sign up to set email alerts
|

Neuroradiological and neuropsychological assessment in anorexia nervosa

Abstract: SynopsisSeventeen patients with anorexia nervosa were examined by computed tomography (CT) and psychometry and compared with ten normal control subjects. The patients were found to have enlarged external cerebrospinal fluid spaces compared to controls. No differences were found in ventricular size and X-ray absorption density measurements between patients and controls. The patients performed abnormally on the symbol digit test, the scores of which displayed a significant negative correlation with the CT scan c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 31 publications
1
45
1
Order By: Relevance
“…Neuroimaging studies with CT reported cerebral atrophy and enlarged ventricles in ill AN (98)(99)(100)(101)(102)(103)(104)(105)(106). In BN similar but less pronounced structural brain abnormalities were reported (107) and may have been related to a chronic dietary restriction.…”
Section: Brain Structurementioning
confidence: 74%
“…Neuroimaging studies with CT reported cerebral atrophy and enlarged ventricles in ill AN (98)(99)(100)(101)(102)(103)(104)(105)(106). In BN similar but less pronounced structural brain abnormalities were reported (107) and may have been related to a chronic dietary restriction.…”
Section: Brain Structurementioning
confidence: 74%
“…Recently, Wagner et al (2003) found a hyper-responsiveness in the parietal lobule in AN subjects, when confronted with their own digitally distorted body images using a computer-based video technique and functional magnetic resonance imaging. Moreover, neuropsychologic studies are consistent with disturbances of parietal function in AN (Horne et al, 1991;Palazidou et al, 1990;Mathias and Kent, 1998;Szmukler et al, 1992;Hamsher et al, 1981). Mesulam (1999) describes a network involving parietal, frontal, cingulate, and limbic pathways that modulate spatial attention.…”
Section: Only Rec An Have Reduced [mentioning
confidence: 81%
“…Findings in clinical populations are inconsistent and limited by small, diagnostically diverse groups and the use of variable outcome measures. [1][2][3] Although most neuropsychological studies in anorexia nervosa (AN) have suggested impairments in higher-level executive, memory, learning, and visuospatial functioning, [3][4][5][6][7][8][9][10][11][12][13] some have not found abnormalities [14][15][16] and others have found superior functioning. [17][18] Some of these studies have lacked a normal control group (NC) 7,12 thereby limiting these findings.…”
Section: Introductionmentioning
confidence: 99%